Prophylactic Effect of Biherbal Extracts of Boerhavia diffusa and Tribulus terrestris in Wistar Rats against Adenine Induced Chronic Kidney Disease: Haemato-Biochemical Profile - Patel, Siddhi G.; Raval, Sunant K.; Dhami, Arjun J.; Bhavsar, Shailesh K. (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
The experiment was carried out to study the prophylactic efficacy of extracts of roots of Boerhavia diffusa (Punarnava) and fruits of  Tribulus terrestris (Gokhru) on adenine induced chronic kidney disease in male Wistar rats. Total 30 mature rats were randomly divided  into 4 groups, group I (normal control, n=6), group II (adenine control group, in which adenine was given @ 200 mg/kg b.wt., daily  orally for 28 days, n=8), while group III and IV served as biherbal prophylactic groups. In group III (n=8) biherbal aqueous extracts (ratio  0.5:1) and in group IV (n=8) biherbal alcoholic extracts (ratio 1:1) of Boerhavia diffusa and Tribulus terrestris were given in 0.5% sodium  bicarbonate solution at the dose rate of 300 mg/kg b.wt. along with adenine solution @ 200 mg/kg b.wt. daily orally for 28 days.  Haematological and serum biochemical parameters were studied on day 0 and 28 of experiment. The mean haemoglobin, TEC, and  lymphocyte counts showed significant decrease and TLC and granulocyte counts showed significant increase in adenine control group  as compared to normal control group after 28 days of treatment. Among serum biochemical parameters, ALT, AST, serum urea nitrogen,  uric acid, creatinine, and phosphorus levels showed significant increase, whereas serum total protein showed significant decrease in  adenine control group as compared to control group on day 28 over day 0. All the haemato-biochemical changes were significantly  prevented in the biherbal prophylactic groups. The result revealed that aqueous and alcoholic biherbal extracts possess prophylactic  and nephroprotective activities, which protected kidneys against adenine induced chronic kidney disease in rats.
Keywords: Boerhavia diffusa; Tribulus terrestris; Biherbal extract